DINAMIKA LINGKUNGAN PESANTREN DAN KECERDASAN EMOSIONAL TERHADAP PRESTASI BELAJAR AKIDAH AKHLAK DI PESANTREN DAARUL FALAAH BANJARNEGARA - Farhan, Frisky Aisya; Firdaus, Firdaus (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2024)
Education is a collaboration between society and educational institutions towards wise and noble values for human progress. The pesantren environment is a significant consideration in realizing the learning progress of mentally and emotionally practical students. Seeing how important the ability to appreciate someone in everyday life is, it must be guided in every learner, one of which is through learning moral creed. The relationship between the ability to understand students and learning moral creed is significant because the ability to understand students essentially lies in character and moral creed. This research is a type of field research. The subjects in this study were boarding school administrators, moral creed teachers, and several students of MTs Muhammadiyah Merden. The data were collected using observation, interview, and documentation methods. The data were analyzed descriptively and qualitatively through data reduction, presentation, and conclusion drawing. The results of this study indicate that 1) the pesantren environment has a strategic role in improving Aqidah akhlak learning achievement because students can be controlled regularly with various daily activities in the pesantren. 2) Emotional intelligence is formed from the students' interaction patterns in several activities and learning in the classroom so that the students can understand and tolerate various differences that arise. 3) The importance of the role of Akidah Akhlak teachers in strengthening emotional intelligence and achievement in Akidah Akhlak learning for students.